Investigating the effect of synthetic cobalt and nickel oxide nanoparticles on the growth and physiology of Mungbean (Vigna radiata L.) seedlings, and exploring tunable magnetism switching behaviour - Anjali Joshi; Simranjeet Kaur; Pargat Singh; Havneet Singh; Keya Dharamvir; Harsh Nayyar; Gaurav Verma (Plant Nano Biology)
The extensive application of metal oxide nanoparticles in industrial and agricultural systems has led to their pervasive accumulation in the environment, raising significant concerns about their phytotoxicity and ecological impacts. This study examines the dual effects of cobalt oxide (CoO) and nickel oxide (NiO) nanoparticles on Mungbean (Vigna radiata L.) seedlings, emphasizing their biological responses and magnetic properties for detection and monitoring applications. Seeds were treated with CoO and NiO nanoparticles at concentrations of 50 and 100 mg/L and cultivated under controlled conditions. Physiological assessments revealed substantial reductions in root growth (28–30 % for CoO; 22–24 % for NiO), shoot growth (9–17 % for CoO; 5–17 % for NiO), relative water content, and chlorophyll levels compared to untreated controls. Nanoparticle uptake and distribution across plant tissues were characterized using vibrating sample magnetometry (VSM), highlighting alterations in magnetic behavior distinct from their intrinsic properties. Structural and compositional analyses via Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and transmission electron microscopy (TEM) confirmed nanoparticle crystallinity, size, and morphology. The interaction of CoO and NiO nanoparticles with plant systems revealed significant modifications in magnetic properties, offering potential avenues for modulating plant growth through external magnetic fields. This study highlights the feasibility of utilizing magnetic oxide nanoparticles to engineer bio-nano magnetic sensors for real-time monitoring of plant health and environmental parameters. Such innovations hold promise for advancing sustainable agricultural practices and enhancing global food security through precision nanotechnology.